2000
DOI: 10.1614/0890-037x(2000)014[0077:wmigag]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Weed Management in Glufosinate- and Glyphosate-Resistant Soybean (Glycine max)1

Abstract: An experiment was conducted at six locations in North Carolina to compare weed-management treatments using glufosinate postemergence (POST) in glufosinate-resistant soybean, glyphosate POST in glyphosate-resistant soybean, and imazaquin plus SAN 582 preemergence (PRE) followed by chlorimuron POST in nontransgenic soybean. Prickly sida and sicklepod were controlled similarly and 84 to 100% by glufosinate and glyphosate. Glyphosate controlled broadleaf signalgrass, fall panicum, goosegrass, rhizomatous johnsongr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
144
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(155 citation statements)
references
References 19 publications
10
144
0
1
Order By: Relevance
“…None of the ammoniumglufosinate treatments were efficient controlling goosegrass. The low efficacy of ammonium glufosinate on goosegrass, especially for plants at advanced development stages, is also reported in other studies (Culpepper and York, 1999;Culpepper et al, 2000). In these works, the maximum control provided by ammonium-glufosinate (490 g ha -1 ) is 60% over plants with 4-8 leaves.…”
Section: Post-emergence -Experimentssupporting
confidence: 68%
“…None of the ammoniumglufosinate treatments were efficient controlling goosegrass. The low efficacy of ammonium glufosinate on goosegrass, especially for plants at advanced development stages, is also reported in other studies (Culpepper and York, 1999;Culpepper et al, 2000). In these works, the maximum control provided by ammonium-glufosinate (490 g ha -1 ) is 60% over plants with 4-8 leaves.…”
Section: Post-emergence -Experimentssupporting
confidence: 68%
“…Other research [17][18][19][20] has demonstrated that atrazine, dicamba, glufosinate, and glyphosate control common ragweed. Differences in Texas panicum density between fields were associated with fewer differences observed between treatments in field 1 compared with more differences among treatments in field 2 ( Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Dicamba alone or in combination with other herbicides can be effective in controlling common ragweed and other broadleaf weeds [16,17]. Dicamba and glufosinate applied to small common ragweed can control this weed effectively and can serve as alternatives to atrazine and glyphosate in corn [8,[17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…A weakness of glyphosate is poor morningglory control (Corbett et al, 2004;Jordan et al, 1997). Another development from the use of glyphosate-tolerant (Roundup Ready ® ) crops has been, in some instances, reduced weed pressure or increased weed species shifts when a Roundup Ready ® crop has been grown for a number of years (Culpepper et al, 2000;Hilgenfeld et al, 2004;Marshall et al, 2000). In these areas, glyphosate has been so effective at controlling weeds that farmers are not concerned with a build-up of weed seed in the soil.…”
Section: Glyphosate And/or Glufosinate-ammoniummentioning
confidence: 99%